Interactions between dietary oil treatments and genetic variants modulate fatty acid ethanolamides in plasma and body weight composition. Issue 6 (25th January 2016) - Pu, Shuaihua; Eck, Peter; Jenkins, David J. A.; Connelly, Philip W.; Lamarche, Benoît; Kris-Etherton, Penny M.; West, Sheila G.; Liu, Xiaoran; Jones, Peter J. H.
Abstract: Fatty acid ethanolamides (FAE), a group of lipid mediators derived from long-chain fatty acids (FA), mediate biological activities including activation of cannabinoid receptors, stimulation of fat oxidation and regulation of satiety. However, how circulating FAE levels are influenced by FA intake in humans remains unclear. The objective of the present study was to investigate the response of six major circulating FAE to various dietary oil treatments in a five-period, cross-over, randomised, double-blind, clinical study in volunteers with abdominal obesity. The treatment oils (60 g/12 552 kJ per d (60 g/3000 kcal per d)) provided for 30 d were as follows: conventional canola oil, high oleic canola oil, high oleic canola oil enriched with DHA, flax/safflower oil blend and corn/safflower oil blend. Two SNP associated with FAE degradation and synthesis were studied. Post-treatment results showed overall that plasma FAE levels were modulated by dietary FA and were positively correlated with corresponding plasma FA levels; minor allele (A) carriers of SNP rs324420 in gene fatty acid amide hydrolase produced higher circulating oleoylethanolamide (OEA) ( P =0·0209) and docosahexaenoylethanolamide (DHEA) levels ( P =0·0002). In addition, elevated plasma DHEA levels in response to DHA intake tended to be associated with lower plasma OEA levels and an increased gynoid fat mass. In summary, data suggest that the metabolic and physiological responses to dietary FA may be influenced via circulating FAE. Genetic analysis of rs324420 might help identify a sub-population that appears to benefit from increased consumption of DHA and oleic acid.